Single and double bundle posterior cruciate ligament reconstruction yield comparable clinical and functional outcomes: a systematic review and meta-analysis : knee - Krott, Nikolas Leon; Wengle, Lawrence; Whelan, Daniel; Wild, Michael; Betsch, Marcel (Knee surgery, sports traumatology, arthroscopy, 2022)
To perform a systematic review and compare the functional and objective outcomes after single-bundle (SB) vs. double-bundle (DB) posterior cruciate ligament reconstruction (PCLR). Where possible to pool outcomes and arrive at summary estimates of treatment effect for DB PCLR vs. SB PCLR via an embedded meta-analysis.